2021
DOI: 10.3389/fevo.2021.789264
|View full text |Cite
|
Sign up to set email alerts
|

Long Distance Seed Dispersal by Forest Elephants

Abstract: By dispersing seeds long distances, large, fruit-eating animals influence plant population spread and community dynamics. After fruit consumption, animal gut passage time and movement determine seed dispersal patterns and distances. These, in turn, are influenced by extrinsic, environmental variables and intrinsic, individual-level variables. We simulated seed dispersal by forest elephants (Loxodonta cyclotis) by integrating gut passage data from wild elephants with movement data from 96 individuals. On averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…However, here we report there are strong human effects across a wide climatic gradient, lending strength to our finding. Human activity has well‐known negative effects on Central African animal communities (Beirne, Nuñez, et al., 2019 ; Koerner et al., 2017 ; Núñez, Froese, et al., 2019 ; Poulsen et al., 2011 , 2017 , 2021 ), and our results suggest that these disturbance gradients are also related to tree community composition, supporting past work suggesting indirect stress on plants and alterations in plant–animal interactions can modify plant community composition (Núñez, Clark, et al., 2019 ; Poulsen et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, here we report there are strong human effects across a wide climatic gradient, lending strength to our finding. Human activity has well‐known negative effects on Central African animal communities (Beirne, Nuñez, et al., 2019 ; Koerner et al., 2017 ; Núñez, Froese, et al., 2019 ; Poulsen et al., 2011 , 2017 , 2021 ), and our results suggest that these disturbance gradients are also related to tree community composition, supporting past work suggesting indirect stress on plants and alterations in plant–animal interactions can modify plant community composition (Núñez, Clark, et al., 2019 ; Poulsen et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both unrestricted and no‐dispersal scenarios are unrealistic, as no plant has either infinite or zero dispersal potential (Cain et al., 2000; Nathan, 2006). The 250 km threshold lies in between unlimited and zero dispersal scenarios and is optimistic given maximal seed dispersal distance tends to be below 100 km (Poulsen et al., 2021, megafauna dispersal). Second, we assumed that only climatic suitability and proximity to an occurrence point constrain the movement of species through the landscape.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, observations in tropical forests show that availability of fruits and other ephemeral resources influence animal abundance and behaviors (Babweteera et al, 2018; Butt et al, 2015; Huang et al, 2012). The abundance of frugivores, critical for the dispersal of many plant species, generally increases when fruiting is abundant (e.g., Gross‐Camp, Masozera, & Kaplin, 2009; Poulsen et al, 2021). Studies in temperate biomes have shown that insect pollinators time their emergence to correspond with local flowering seasons with a general tendency for insects at higher elevations to emerge later than those at lower elevations (Bartomeus et al, 2011; Forrest, 2016; Forrest & Thomson, 2011).…”
Section: Introductionmentioning
confidence: 99%